Clinical Outcomes of Laparoscopic Appendectomy in Complicated Appendicitis among Young Children - Tariq Hayat Khan, Syed Aamer Hussain, Ali Gohar Khan, Tariq Jamil, Fazal Hussain, Summar Fatima (Pakistan Journal of Medical & Health Sciences, 2023)
Background and Aim: Despite the good outcomes associated with laparoscopic appendectomy for uncomplicated appendicitis, the benefits of this procedure for complicated appendicitis are less obvious due to increased infection risk. The current study aims to assess the effectiveness of laparoscopic appendectomy in children with complicated appendicitis. Patients and Methods: This retrospective study was conducted on 92 complicated appendicitis cases among young children (<8 years) in the department of Surgery, Lady Reading Hospital, Peshawar for the period from January 2022 to June 2022. Prior to study conduction, surgical consent was provided by each individual. Demographic details such as age and gender, operative time, hospital stay, operative finding, postoperative complications, bowel function return, and oral feed resumption were recorded. Results: Of the total 92 cases, 52 (56.5%) were male and 40 (43.5%) were females. The overall mean age was 5.9±0.8 years with an age range from 4.2 to 7.8 years. Among the total cases, 88 (95.7%) underwent complete laparoscopic appendectomy whereas 4 (4.3%) patients needed conversion to open appendectomy. The mean length of hospitalization was 4.8±3.3 days. The operation took 72.8±26.4 minutes. In terms of postoperative complications, the incidence of post-operative ileus, superficial wound infections, and intra-abdominal collections developed in 4 (4.3%), 2 (2.2%), and 6 (6.5%) respectively. There was no death recorded. Conclusion: The present study concluded that children with complicated appendicitis can benefit from laparoscopic appendectomy. In addition to its feasibility, safety, rapid recovery and good cosmetic results, this procedure is associated with minimal post-operative morbidity. Keywords: Complicated appendectomy, Laparoscopic appendectomy, Clinical outcomes